2017
DOI: 10.1002/ajp.22632
|View full text |Cite
|
Sign up to set email alerts
|

Factors of influence and social correlates of parturition in captive Campbell's monkeys: Case study and breeding data

Abstract: How nonhuman primates deal with birth, at the moment of delivery, and during the following days, remains poorly explored because of the unpredictability of this event, particularly for forest-dwelling arboreal species. Available studies highlight intra- and interspecific variation which suggest flexibility of the timing of delivery, of behavior associated with labor contractions and parturition, and the social context and ambient noise surrounding delivery. Here, we present the findings of a two-decade survey … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 55 publications
(100 reference statements)
0
3
0
Order By: Relevance
“…The results from the laboratory studies are also not consistent. Of the three primate colonies examined by McGrew and McLuckie (1984), only one showed the weekend effect and both this colony and the one examined by Lemasson et al (2017) had low sample sizes ( n < 50). Of the two studies that had larger sample sizes, only the one by Alford et al (1992) showed a weekend effect.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…The results from the laboratory studies are also not consistent. Of the three primate colonies examined by McGrew and McLuckie (1984), only one showed the weekend effect and both this colony and the one examined by Lemasson et al (2017) had low sample sizes ( n < 50). Of the two studies that had larger sample sizes, only the one by Alford et al (1992) showed a weekend effect.…”
Section: Discussionmentioning
confidence: 74%
“…They attributed this pattern to the stressful effects of routine laboratory procedures occurring during the week, which were greatly reduced on weekends. Finally, in a laboratory colony of Campbell's monkeys ( Cercopithecus campbelli ), analysis of 34 births again showed that significantly more births occurred on weekends than during the week, and this also was attributed by the authors to the disruption caused by laboratory procedures during the week (Lemasson et al, 2017).…”
Section: Introductionmentioning
confidence: 98%
“…In conventional usage, they are considered to contradict each other. For example, Lemasson, Jubin, Bec, and Hausberger (, p. 4), examining behavior of Campbell's monkeys, conclude that following delivery of an infant, social play by the mother decreased ( Z = 2.03, p = 0.043), but call exchanges “did not” ( Z = 1.72, p = 0.09).…”
Section: Flaws In the Corementioning
confidence: 99%